2011
DOI: 10.2147/oaem.s14307
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behaviors in the psychiatric emergency service

Abstract: Introduction:Studies of aggressive behaviors in a nonforensic mental health setting have focused primarily on the inpatient ward and, on event prediction, using behavior-based clinical rating scales. Few studies have specifically targeted aggressive behaviors in the psychiatric emergency service or determined whether assessing the demographic and clinical characteristics of such patients might prove useful for their more rapid identification.Methods:We used a prospectively acquired database of over 20,900 visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
1
9
0
6
Order By: Relevance
“…Our results also support those of previous studies showing that alcohol is primarily responsible for most substance misuse-related PES visits. 2,29,33 As in the present study, Curran el al. 2 reported a slight predominance of depressive disorders in their substance misuse comorbid patients.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our results also support those of previous studies showing that alcohol is primarily responsible for most substance misuse-related PES visits. 2,29,33 As in the present study, Curran el al. 2 reported a slight predominance of depressive disorders in their substance misuse comorbid patients.…”
Section: Discussionsupporting
confidence: 80%
“…The completed forms were forwarded to the principal investigator on a weekly basis for data entry. 28,29 As in our earlier reports, 28,29 many strategies were used in order to minimize diagnostic uncertainty. First, over 60% of visits have been shown to occur within the daytime hours at these sites, which were covered (during the weekdays) by regular psychiatric staff each with over 5 years' experience in the PES setting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Chaput et al reported that only 7.4% of visits to participating psychiatric emergency services in Quebec, Canada were marked by current aggression. 19 Furthermore, our study found the violent cohort to be significantly associated with the male gender and substance use.…”
Section: Discussionmentioning
confidence: 56%
“…There was broad geographical variation in the primary studies: 13 were conducted in Australia, three were from the USA, three from the UK, and a study each from Canada, Cyprus, Italy, Jordan, Lebanon, Morocco, Nigeria, Palestine, Singapore, and Taiwan . Twenty‐seven (93%) studies scored 50–100% in the mixed methods appraisal tool indicating moderate to high quality.…”
Section: Resultsmentioning
confidence: 99%